ANALISIS PELANGGARAN KESANTUNAN BERBAHASADI INSTAGRAM SEBAGAI MATERI AJAR DIGITAL PRAGMATIK UNTUK PENINGKATAN LITERASI KRITIS - Putra, Listya Buana; Markhamah, Markhamah; Sabardila, Atiqa (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Abstract: This study aims to describe the forms of language politeness violations that appear in the Instagram comment column as pragmatic digital teaching materials to improve critical literacy. The background of this research departs from the phenomenon of public communication on social media which tends to be free and minimally controlled. Instagram, as the dominant social media among teenagers and young adults, is a representative space to examine polite and polite language practices in the digital realm. With a qualitative descriptive approach, data was obtained through documentation of comments on public posts on Instagram and analyzed using Leech's theory of politeness. The results of the analysis show that the dominant forms of offense include violations of the maxim of praise, sympathy, approval and discretion, as well as the context of use closely related to political topics. These findings provide an idea that even though it takes place in a free online space, the practice of politeness is still present and can be studied scientifically to enrich pragmatic understanding, as well as become a reference in the development of digital media-based language learning to improve critical literacy. Keywords: instagram; politeness; critical literacy; teaching materials; pragmatics